ChemInform Abstract: Pd‐Catalyzed Threefold Arylations of Mono‐, Di‐ and Tetra‐Bromoquinones Using Triarylbismuth Reagents. Issue 15 (25th March 2013) - Rao, Maddali L. N.; Giri, Somnath
Abstract A few highlights of the title one‐pot reaction are the use of non‐toxic and air stable triarylbismuths, the operational simplicity, short reaction times, mild conditions, and the tolerance of a wide variety of substrates.